Admission Blood Pressure as Predictors of Thirty Days Mortality in Community Acquired Pneumonia in a Tertiary Care Hospital of Bangladesh - Islam, Md Khairul; Hossain, Md Monoar; Khatun, Sheikh Jamila; Hossain, Fahima Sharmin; Zuhora, Fatematuz; Rashid, Md Mamunur; Zaman, Mohammad Monir uz (Journal of Medicine, 2025)
Background: Assessing admission blood pressure (BP) is crucial in predicting mortality community acquired pneumonia. Methodology: This was a prospective longitudinal study at DMCH to explore hemodynamic predictors of the 30-day all-cause mortality, including deaths during hospital stay and after discharge in community-acquired pneumonia. Statistical analyses included the Z-proportion test, multivariate logistic regression, and ROC curve analysis. A p-value of less than 0.05 was considered statistically significant. Results: The study's hospital mortality rate in community-acquired pneumonia was 14%. However, the all-cause mortality rate after 30 days of hospital admission increased to 22.6%. This was significantly associated with systolic blood pressure below 90 mmHg, diastolic pressure of 60 mm Hg or less, pulse of 40 mm Hg or less, and mean arterial pressure below 70 mm Hg (p<0.001). The multivariate logistic regression analysis indicated a significant association between blood pressure parameters and 30-day mortality in community-acquired pneumonia (CAP) patients. Systolic blood pressure (<90 mmHg) was found to be a significant predictor, with an Odds Ratio (OR) of 5.439 (95% CI: 1.565 to 18.895) and a p-value of 0.004. This suggests a significantly higher risk of mortality for subjects with systolic blood pressure below 90 mmHg compared to those with higher readings. However, diastolic blood pressure (<60 mmHg) did not show any significant association, as indicated by an OR of 0.871 (95% CI: 0.336 to 2.256) and a p-value of 0.775. Similarly, pulse pressure (<40 mmHg) did not exhibit any significant relationship with mortality, with an OR of 0.756 (95% CI: 0.090 to 6.377) and a p-value of 0.797. On the other hand, mean arterial pressure (<70 mmHg) emerged as another significant predictor, with an OR of 4.465 (95% CI: 1.280 to 15.579) and a p-value of 0.012. This suggests a significantly higher risk of mortality among subjects with mean arterial pressure below 70 mmHg compared to those with higher values. Conclusion: Low systolic blood pressure (<90 mmHg) and mean arterial pressure (<70 mmHg) are associated with increased mortality risk in CAP patients. J MEDICINE 2025; 26: 13-19